Indonesian Policy Choices on Salt - Vince Tebay (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is one of the salt importing countries in Asia. This study aims to review the root causes of the salt import policy chosen by the government. Meanwhile, on the other hand, domestic salt farmers are in a subordinate position. This research is a type of qualitative research that uses a literature study approach. The source of the data in this study therefore comes from previous studies in the form of journals and books. Data collection techniques in this study used observation and documentation techniques. Data analysis was carried out through three stages; reducing data, presented, and drawing conclusions. The examination uses a research approach and previous research. This research is a starting point for further review and future policy agendas.